Cooperation of IRAK1/4 inhibitor and ABT-737 in nanoparticles for synergistic therapy of T cell acute lymphoblastic leukemia [Corrigendum] - Wu X (Dove Medical Press, 2018)
Wu X, Wang L, Qiu Y, Zhang B, Hu Z, Jin R. Int J Nanomedicine. 2017;12:8025–8034.On page 8025, the first affiliation was listed as “Department of Pediatrics, Union Hospital, Tongji Medical College, University of Science and Technology, Wuhan” however it should have been “Department of Pediatrics, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, China”.Read the original article